The effects of strength training on some parameters of aerobic and anaerobic endurance - Šentija, Davor (Array, 2009)
Abstract: The studies exploring the influence of resistance training on endurance in men have produced inconsistent results. The aim of this study was to examine the influence of an Olympic weight lifting training programme on parameters of aerobic and anaerobic endurance in moderately physically active men. Eleven physical education students (age: 24.1 ± 1.8 yr, height: 1.77 ± 0.04 m, body mass: 76.1 ± 6.4 kg; X ± SD) underwent a 12-week, 3 times/wk training programme of Olympic weight lifting. Specific exercises to master the lifting technique, and basic exercises for maximal strength and power development were applied, with load intensity and volume defined in relation to individual maximal load (repetitio maximalis, RM). Parameters of both, aerobic and anaerobic endurance were estimated from gas exchange data measured during a single incremental treadmill test to exhaustion, which was performed before, and after completion of the 12-wk programme. After training, there was a small, but significant increase in body mass (75.8 ± 6.4 vs. 76.6 ± 6.4, p<0.05) and peak VO2 (54.9 ± 5.4 vs. 56.4 ± 5.3 mL O2/min/kg, p<0.05), with no significant change of the running speed at the anaerobic threshold (VAT) and at exhaustion (Vmax) (both p>0.05). However, there was a significant increase of anaerobic endurance, estimated from the distance run above VAT, from VAT to Vmax (285 ± 98 m vs 212 ± 104 m, p<0.01). The results of this study indicate that changes in both, anaerobic and aerobic endurance due to a 12-wk period of strength training in untrained persons can be determined from a single incremental treadmill test to exhaustion. The possible causes of those training effects include several possible mechanisms, linked primarily to peripheral adaptation